PHARMACOECONOMIC EVALUATION OF THE MEDICINAL PRODUCTS ERLOTINIB, DOCETAXEL, PEMETREXED AND GEFITINIB IN THE SECOND-LINE TREATMENT OF LOCALLY-ADVANCED OR METASTATIC NON-SMALL-CELL LUNG CANCER - A. U. Kulikov (Фармакоэкономика)
Abstract: lung cancer takes the second place in the general structure of incidence of malignant neoplasms in Russia. The diagnosis of a local or metastatic non small cells lung cancer (NSCLC) serves the indication to carrying out the 1st line chemotherapy. In case of progressing against or after the 1st line chemotherapy the 2nd line of treatment of NSCLC is carried out. As the 2nd line of monotherapy of NSCLC there are used docetaxel or pemetrexed and representatives of a class of target oral medicines – gefitinib and erlotinib. This article presents results of comparative pharmacoeconomical estimation of this medicines in real modern health care system of Russian Federation. According to the obtained results application of erlotinib as the 2nd line therapy of patients with local or metastatic NSCLC is more preferable than docetaxel, pemetrexed or gefitinibfrom the economic point of view.